THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION, DIGITAL ENTREPRENEURSHIP AND GENDER ON ENTREPRENEURIAL INTEREST - Auliadara, Nurul; Sojanah, Janah; Purnamasari, Imas (Universitas Muhammadiyah Surakarta, 2024)
This study focuses on the Influence of Entrepreneurship Education, Digital Entrepreneurship and gender on students' interest in entrepreneurship at the Geology and Mining Polytechnic